The Effectiveness of Acquaintance Therapy on Improving Interaction Skills in Clients with Social Isolation at Radjiman Wediodiningrat Hospital - Enggal Hadi Kurniyawan; Setyowati Nurrohmah; Robby Prihadi Aulia Erlando; Amalia Kusumaningsih (KHD Production, 2025)
Hebephrenic schizophrenia presents with symptoms such as disorganized thinking, emotional disturbances, and behavioral issues that often lead to social isolation. Clients experiencing social isolation demonstrate impaired interpersonal relationships and a tendency to withdraw from social settings. Acquaintance therapy is a psychiatric nursing intervention conducted gradually to enhance the client's social interaction capabilities. This study aims to determine the effectiveness of acquaintance therapy in improving interaction skills in a client with social isolation at Garuda Ward, Radjiman Wediodiningrat Hospital, Lawang, Malang. Using a case study design, this research involved a 30-year-old male client diagnosed with hebephrenic schizophrenia and social isolation. The intervention was conducted over six consecutive days, lasting 15 to 30 minutes each. Data collection included observation, interviews, and nursing documentation. The study revealed a significant improvement in the client interaction skills after the intervention, with symptoms of social isolation reducing from 13 to 2. The client could introduce himself, converse with others, and participate in group activities. These findings indicate that acquaintance therapy is effective in enhancing social interaction in clients with social isolation and can be considered a recommended non-pharmacological approach in psychiatric nursing practice.